Financial development and the effectiveness of monetary policy - Ma, Yong; Lin, Xingkai (Journal of Banking & Finance, 2016)
This paper investigates the relationship between financial development and the effectiveness of monetary policy using panel data from 41 economies. The results show that the effects of monetary policy on output and inflation are significantly and negatively correlated with financial development, indicating that the effectiveness of monetary policy declines as the financial system becomes more developed. This finding is robust across all the different specifications and estimation methods examined. Our paper provides new evidence and insights to the long-standing debate on the relationship between financial development and the effectiveness of monetary policy.